Study on decomposition kinetics of activated alunite concentrate from copper tailings and leaching behavior of valuable elements - Ling Liu (Elsevier, 2021)
Alunite flotation concentrate extracted from copper tailings is considered to be a resource for recovery of potassium, aluminum and gallium, which mainly contains alunite, quartz, dickite and pyrite phases by the X-ray diffraction analysis. The calcination temperature and time affect not only the decomposition ratio of alunite but also the phase change of alumina. The effects of mechanical activation on thermal decomposition and leaching behavior of the alunite concentrate are investigated. The decomposition reactions of pyrite and alunite happen at 400–500 °C and 500–800 °C respectively, and the decomposition of alunite involves two stages, dehydration and desulphation. The mechanical activation produces some amorphisation and structural disordering, which is responsible for the decrease of apparent activation energy of dehydration as well as desulphation. The leaching ratio of potassium, aluminum and gallium increases with activation time.